Transition-Metal-Free Suzuki–Miyaura Coupling Reaction of Arylpropargylic Bromides with Aryl- and Alkenylboronic Acids - Ueda, Mitsuhiro; Nishimura, Kota; Ryu, Ilhyong (Synlett, 2013)
In the absence of transition-metal catalyst, Suzuki–Miyaura coupling reaction between aryl- and alkenylboronic acids and arylpropargylic bromides proceeded to give the corresponding acetylenic products selectively.
Keywords: regioselective; propargylation; transition-metal-free; C–C bond formation; aryl- and vinylboronic acids